Companion to Heidegger's Contributions to philosophy - Scott, Charles E. (Studies in Continental thought., 2001)
This is an indispensable book for scholars and students of Heidegger, but it is also one of the most difficult because of its aphoristic style and new and strange words. Here an international group of 14 Heidegger scholars share strategies for reading and understanding this challenging work. Overall approaches for becoming familiar with Heidegger's unique language and thinking are included along with detailed readings of key sections of the work.